POLITIK HUKUM TERHADAP INTEGRASI KEADILAN RESTORATIF DALAM PRAKTIK PENEGAKAN HUKUM DI INDONESIA - Husnayain, Nazla (Universitas Labuhanbatu, 2025)
This study provides a critical perspective on the role of legal policy actors in shaping the restorative justice paradigm in Indonesia. Criminal justice reform in Indonesia requires the implementation of restorative justice concepts. This study aims to evaluate the role of legal policy in guiding the adoption of restorative justice and to assess the compatibility of restorative policies with national criminal law principles. The research method used is normative qualitative, employing a document study approach that includes analysis of the Criminal Procedure Code (KUHAP), Supreme Court Regulations, and Police Chief Regulations. The results of the study indicate that the regulatory framework has provided substantive support, but the effectiveness of implementation is still hampered by technical guidelines that are not yet detailed, uneven distribution of resources, and the tendency of law enforcement officials to use a retributive approach. The findings also reveal that the integration between formal and informal mechanisms is not yet optimal, so that the protection of victims' rights and the principle of proportionality of restorative intervention are not consistently applied.Keywords: Legal politics; Restorative Justice; Criminal Justice System.